Rapid aneuploidy diagnosis by multiplex ligation-dependent probe amplification and array comparative genomic hybridization in pregnancy with major congenital malformations - Chih-Ping Chen; Yi-Ning Su; Shin-Yu Lin; Chih-Long Chang; Yeou-Lih Wang; Jiau-Pei Huang; Chen-Yu Chen; Fang-Yu Hung; Yi-Yung Chen; Pei-Chen Wu; Wayseen Wang (Elsevier, 2011)
Objective: To report five cases of major congenital malformations associated with common aneuploidies detected by rapid aneuploidy diagnosis. Case Reports: The fetus in the first case presented cebocephaly, semilobar holoprosencephaly, and tetralogy of Fallot on ultrasound at 25 gestational weeks. Cordocentesis using multiplex ligation-dependent probe amplification to detect aneuploidies of chromosomes X, Y, 13, 18, and 21 in uncultured cord blood revealed three copies of all targets on chromosome 13 consistent with the diagnosis of trisomy 13. The fetus in the second case presented bilateral choroid plexus cysts, congenital diaphragmatic hernia, and club foot on ultrasound at 18 gestational weeks. Amniocentesis using array-based comparative genomic hybridization (aCGH) in uncultured amniocytes revealed a gain in the DNA dosage of chromosome 18 consistent with the diagnosis of trisomy 18. The fetus in the third case presented aortic stenosis and nuchal edema on ultrasound at 22 gestational weeks. Amniocentesis using aCGH in uncultured amniocytes revealed a result of monosomy X and Turner syndrome. The fetus in the fourth case presented nuchal cystic hygroma and ventriculomegaly on ultrasound at 17 gestational weeks. Amniocentesis using aCGH in uncultured amniocytes revealed a gain in the DNA dosage of chromosome 21 consistent with the diagnosis of trisomy 21. The fetus in the fifth case presented holoprosencephaly, omphalocele, and hydronephrosis on ultrasound at 17 gestational weeks. Amniocentesis using aCGH in uncultured amniocytes revealed a gain in the DNA dosage of chromosome 13 consistent with the diagnosis of trisomy 13. Conclusions: Prenatal diagnosis of major congenital malformations should alert one to the possibility of chromosomal abnormalities. Multiplex ligation-dependent probe amplification and aCGH have the advantage of rapid aneuploidy diagnosis of common aneuploidies in cases with major congenital malformations.